2007
DOI: 10.1068/p5617
|View full text |Cite
|
Sign up to set email alerts
|

Seeing beyond the Target: Environmental Context Affects Distance Perception

Abstract: It is commonly assumed that perceived distance in full-cue, ecologically valid environments is redundantly specified and approximately veridical. However, recent research has called this assumption into question by demonstrating that distance perception varies in different types of environments even under full-cue viewing conditions. We report five experiments that demonstrate an effect of environmental context on perceived distance. We measured perceived distance in two types of environments (indoors and outd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
51
0
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(64 citation statements)
references
References 13 publications
5
51
0
8
Order By: Relevance
“…For example, Witt et al (2007) reported that egocentric distance judgments were approximately 10 % larger when there was little open space beyond the target object, compared to when there was considerable open space beyond the target. Therefore, the effect of the VE manipulation in the current project could have been partially caused by the amount of open space beyond the targets.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Witt et al (2007) reported that egocentric distance judgments were approximately 10 % larger when there was little open space beyond the target object, compared to when there was considerable open space beyond the target. Therefore, the effect of the VE manipulation in the current project could have been partially caused by the amount of open space beyond the targets.…”
Section: Resultsmentioning
confidence: 99%
“…Anecdotal evidence from our laboratory suggests that egocentric distance perception varies considerably across VEs. Studies in the real world indicate that the environmental context influences perceived egocentric distance (Witt, Stefanucci, Riener, & Proffitt, 2007). The current project compared the relationship between frontal and depth extents in two VEs: the indoor classroom environment used by Geuss et al (2012) and a barren outdoor environment consisting of a ground plane covered in a grass texture, which has produced relatively large underperception of egocentric distance in our laboratory (Kelly, Hammel, Siegel, & Sjolund, 2014).…”
mentioning
confidence: 99%
“…In general, participants underestimated the distance to the suspect. However, whereas the AR group showed underestimations of less than 20% (comparable with earlier studies of Proffitt et al, 2003 andWitt et al, 2007), the VR group showed underestimations of almost 30% (Figure 2). These findings confirm earlier observations of Mann et al (2010;see also Króliczak et al, 2006see also Króliczak et al, , 2007 and seem to support the idea that perceptual accuracy is reduced when the nature of responses is less action specific (Milner & Goodale, 1995;Van der Kamp et al, 2008).…”
Section: Discussionmentioning
confidence: 59%
“…perceived shooting distance), directly after finishing each condition (LT and HT), we asked the participants to turn 60 to the left and provide an estimate of the actual shooting distance by positioning an experimenter at the exact same distance from them ( Figure 1). To achieve this, the participants ordered the experimenter to move backward and forward until the experimenter stood at the same distance from them as the suspect had stood at the exact moment of their shot (see Proffitt et al, 2003, andWitt et al, 2007, for similar measures of perceived distance). After reaching a final position, the participants were explicitly asked to confirm whether the experimenter stood at the right distance and to make adjustments when necessary.…”
Section: Perceived Shooting Distancementioning
confidence: 99%
See 1 more Smart Citation